2009
DOI: 10.1177/0267659109347404
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative screening and management of carotid artery disease in patients undergoing cardiac surgery

Abstract: Careful clinical examination together with detailed previous history taking can identify the majority of patients with CAS. Further data are required for the construction of a scientifically valid policy as a guideline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…However, low specificity would seem to dictate ultrasound screening, and possibly additional confirmatory testing 4 of a large proportion of these patients, to alleviate a false-positive diagnosis. On the other hand, carotid duplex ultrasound screening, whether selective or nonselective, identifies only a minority of patients who will develop perioperative stroke, and intervening for those with carotid disease might not decrease the risk of these neurologic events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, low specificity would seem to dictate ultrasound screening, and possibly additional confirmatory testing 4 of a large proportion of these patients, to alleviate a false-positive diagnosis. On the other hand, carotid duplex ultrasound screening, whether selective or nonselective, identifies only a minority of patients who will develop perioperative stroke, and intervening for those with carotid disease might not decrease the risk of these neurologic events.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral artery disease, cerebrovascular disease (prior stroke or transient ischemic attack), and old age were the risk factors most consistently identified in these studies. 2–4,6,37,7681 Applying carotid disease–screening algorithms to cohorts of ultrasound-screened patients undergoing CABG showed that most who had significant carotid artery stenosis could be detected. 5,77,82 Thus, Durand and colleagues 5 found that a risk-profiling algorithm based on a prior stroke or transient ischemic attack, carotid bruit on exam, or age >65 years would have missed significant carotid disease in only 2.3%of patients undergoing CABG (26 of 1138), although this represented 17% of 152 patients with significant carotid disease, and 582 had a false-positive result.…”
Section: Detecting Carotid Artery Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that the risk of occurrence of ICV during CABG is in direct correlation with the degree of carotid stenosis (14). As a consequence a common strategy for the treatment of such patients was "carotid before coronary" that is, first, an operation on the carotid arteries (CEA) and only then CABG in two parts, or as a simultaneous operation (15). However, in patients with significant stenosis of the main tree of the left coronary artery, "left main stenosis" (LMS) and carotid stenosis, priority is given to CABG, primarily because of the seriousness of the location of the stenosis, the symptoms, the possibility of hemodynamic instability, which is rather frequent in those patients, as well as because of the operation itself.…”
Section: Introductionmentioning
confidence: 99%
“…Anastasiasdis et al evaluated carotid arteries in 307 patients undergoing CABG and reported that while 3 out of 4 patients undergoing CABG had carotid atherosclerosis, the majority of these (63%) had < 50% ECAS. (Anastasiadis, Karamitsos et al 2009). Various studies have reported the incidence of ECAS with varies degree of stenosis among the patient populations undergoing CABG which are summarized in table 1.…”
Section: Introductionmentioning
confidence: 99%